Trajectories of Depressive Symptoms Throughout the Peri- and Postpartum Period: Results from the First Baby Study - McCall-Hosenfeld, Jennifer S. (J Womens Health (Larchmt), 2016)
Background: Postpartum depression (PPD) is a common complication of childbearing, but the course of PPD is not well understood. We analyze trajectories of depression and key risk factors associated with these trajectories in the peripartum and postpartum period. Methods: Women in The First Baby Study, a cohort of 3006 women pregnant with their first baby, completed telephone surveys measuring depression during the mother's third trimester, and at 1, 6, and 12 months postpartum. Depression was assessed using the Edinburgh Postnatal Depression Scale. A semiparametric mixture model was used to estimate distinct group-based developmental trajectories of depression and determine whether trajectory group membership varied according to maternal characteristics. Results: A total of 2802 (93%) of mothers completed interviews through 12 months. The mixture model indicated six distinct depression trajectories. A history of anxiety or depression, unattached marital status, and inadequate social support were significantly associated with higher odds of belonging to trajectory groups with greater depression. Most of the depression trajectories were stable or slightly decreased over time, but one depression trajectory, encompassing 1.7% of the mothers, showed women who were nondepressed at the third trimester, but became depressed at 6 months postpartum and were increasingly depressed at 12 months after birth. Conclusions: This trajectory study indicates that women who are depressed during pregnancy tend to remain depressed during the first year postpartum or improve slightly, but an important minority of women become newly and increasingly depressed over the course of the first year after first childbirth.